Merawat Tradisi Bermantra Sebelum Mengaji: Studi Living Qur’an Di Lembaga Tahfidz Pondok Pesantren - Najiburrohman, Najiburrohman; Fauziyah, Ummi (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2023)
Al-Quran is a holy book containing various theological and social teachings that guide humans towards a path pleasing to God. It is just that when the Koran was present and consumed by the public, it experienced various responses which were implemented in the many practices of the living Koran by positioning the Koran beyond its capacity as a text in life. These phenomena seem to be concrete indicators of the expression often labelled on the Koran that it is a righteous book or has relevance to various situations and conditions. This article examines the practice of living the Al-Quran at the Tahfidz Institute of Pondok Pesantren Zainul Anwar Alassumur Kraksaan Probolinggo. The method used in this research is descriptive-qualitative and is included in the type of field research. In exploring data sources, researchers use various instruments, such as interviews, observations, and documentation or studies of related documents. The research shows that; The recitation of Surah Thaha (20): 25-28 at the Zainul Anwar Islamic Boarding School Tahfidz Institute is one of the steps to bring the Al-Qur'an to life in everyday life as a form of hope to Allah SWT. always to provide convenience, blessings, and the benefits of the knowledge you have, because nowadays many people are knowledgeable but cannot practice it in everyday life